Pemanfaatan Karbon Aktif Kulit Kacang Tanah untuk Menurunkan Kadar Ion logam Ca2+ dan Mg2+ dalam Air: Utilization Peanut Shell Activated Carbon to Reduce Levels of Ca2+ and Mg2+ in Water - Wilda Yanti; Husain Sosidi; Indriani; Prismawiryanti; Dwi Juli Puspitasari; Moh. Mirzan; Erwin Abdul Rahim; Nov Irmawati Inda (KOVALEN: Jurnal Riset Kimia, 2023)
Peanut shell has a high cellulose content as a carbon source which can be used as a basic ingredient for making activated charcoal. Research on peanut shells used as activated charcoal aims to determine the effect of contact time and pH on reducing levels of metal ions Ca2+ and Mg2+ in water. The research was conducted using contact time variables (30, 60, 90, 120, and 150 minutes) and pH (4, 5, 6, 7, and 8). Measurement of adsorbed metal levels was determined by using an Atomic Absorption Spectrophotometer (AAS). The research results obtained showed that variations in contact time could reduce Ca2+ levels by 77.46% -84.89% and Mg2+ by 86.88%-88.91%. Adsorbents with variations in pH can reduce Ca2+ levels by 63.48%-88.74% and Mg2+ by 90.35%-94.49%. The best conditions for the absorption of Ca2+ and Mg2+ ions were a contact time of 60 minutes and pH 4. The adsorbent was applied to reduce Ca2+ and Mg2+ levels in water with different hardness levels. The results of the analysis of water samples from two different locations had Ca2+ levels of 94.180 mg/L and 210.20 mg/L, while Mg2+ levels were 13.536 mg/L and 17.420 mg/L. The percentages of Ca2+ adsorption for the two samples were 96.19% and 77.08%, and the percentages of Mg2+ adsorption for the two samples were 21.16% and 10.63%. Carbon from peanut shells activated with sodium acetate has the potential to be used to reduce hardness in water.